COMPARATIVE ANALYSIS OF SPORTS PRACTICE AS MEANS OF SOCIALIZATION OF KHARKIV AND LWIW CITIZENS IN THE 20s – 30s of ХХth CENTURY. - N., Saltan; O., Saltan; Y., Semenova; O., Orlenko; G., Goncharov (Hileya: Scientific Bulletin / Gileya, 2022)
The article aims to analyze the impact of physical culture and sports on the socialization and sociocultural development of the individual in the 1920s – early 1930s. Research methods: analysis, generalization and systematization of data; historical, logical, problem-searching. Due to a large-scale propaganda campaign, there have been systemic changes in the organization of forms of physical activity of citizens and the broad involvement of young people in material culture. In the USSR, under the influence of Soviet propaganda, military-applied sports became popular, and the military nature of the activities of some sports associations in Lviv was associated with the national liberation struggle. If in the Soviet Union the initiative came from the state, the events in the physical culture and sports movement in Galicia were amateur and based on the activities of sports clubs and societies, were the result of public demand. Mostly young people and children took part in active sports, and the fan movement covered all age groups. Playing sports had a positive effect on the formation of personality, instilling a sense of patriotism, strong-willed traits, selfdiscipline, and values of collectivism. Sports training has improved the health of citizens. The sports movement acted as a way to the emancipation of women. Involving people with hearing impairments in sports practices helped them overcome social exclusion. Exercise and sports served as a substitute for socially unacceptable behaviours.